A Study On Alcohol Consumption Among Youth (PUSA Journal of Hospitality and Applied Sciences, 2015)
Background: India has seen a rapid proliferation of city bars and nightclubs in recent years, is fast  shedding its inhibitions about alcohol and lifestyle choices. This situation has led to fears of an  undocumented rise in alcohol abuse not only among poorer classes but others too. Objective: To find  out the prevalence of alcohol consumption among youth. Methods: Survey design was adopted. Data  was collected from n=99 subjects through online sampling. Results: Prevalence of alcohol  consumption was found to be high as majority of males (74.64%) and females (85.7%) reported to  consume alcohol.
Keywords: Alcohol; Youth; Male; Female